Testing Techniques and Fatigue of Additively Manufactured Inconel 718 – A Review (International Journal of Engineering Materials and Manufacture, 2020)
Additive Manufacturing (AM) of metallic components shows unfavorable properties in their as-built state; surface roughness, anisotropy, residual stresses, and internal /surface defects are common issues that affect dynamic properties of AM metals. This paper reviews traditional fatigue testing techniques, summarizes published fatigue data for wrought and additively manufactured metals with focus on Inconel 718. Surface and volume defects of AM metals were presented and how post processing techniques could improve fatigue performance were shown. Different methods for normalizing fatigue data were explored due to varying results of different fatigue testing techniques.